# how can i solve this

• Aug 6th 2008, 08:45 AM
makaveli89
how can i solve this

8/ x²-4 + 6/ 3x -6 =

i know the first step, which is:

8*(3x-6) + 6*(x²-4) / (x²-4)*(3x-6)

but then, i dont know what to do
• Aug 6th 2008, 09:10 AM
nikhil
Quote:

Originally Posted by makaveli89

8/ x²-4 + 6/ 3x -6 =

i know the first step, which is:

8*(3x-6) + 6*(x²-4) / (x²-4)*(3x-6)

but then, i dont know what to do

8/ x²-4 + 6/ 3x -6 =???
Well mathematically your first step is right!
• Aug 6th 2008, 09:11 AM
Simplicity
Quote:

Originally Posted by makaveli89

8/ x²-4 + 6/ 3x -6 =

i know the first step, which is:

8*(3x-6) + 6*(x²-4) / (x²-4)*(3x-6)

but then, i dont know what to do

$\displaystyle \frac{8}{x^2-4} + \frac{6}{3x-6}$

$\displaystyle =\frac{(8)(3x-6) + (6)(x^2 - 4)}{(x^2-4)(3x-6)}$

$\displaystyle =\frac{6x^2 +24x -72}{(x^2-4)(3x-6)}$

$\displaystyle =\frac{(6)(x^2 + 4x - 12)}{(3)(x+2)(x-2)(x-2)}$

$\displaystyle =\frac{(6)(x-2)(x+6)}{(x+2)(3)(x-2)^2}$

Can you simplify and finish the question off now? :)